Good Life, Dignity, Recognition - Carrillo Castillo, Lucy (Estudios de Filosofía, 2004)
The article reflects upon the link between the notions ofgood life, dignity and, recognition. With this purpose, the text has been divided in thefollowing sections: I. The idea of a good life and the pursuit of happiness. 2. The indigence of the real and the question about the meaning of life. 3. Philosophers and the idea of a good life. 4. Good life, recognition and the Kantian concept ofdignity.